2012
DOI: 10.1080/08897077.2011.640160
|View full text |Cite
|
Sign up to set email alerts
|

Baylor SBIRT Medical Residency Training Program: Model Description and Initial Evaluation

Abstract: The Baylor College of Medicine SBIRT Medical Residency Training Program is a multilevel project that trains residents and faculty in evidenced-based screening, brief intervention, and referral to treatment (SBIRT) methods for alcohol and substance use problems. This paper describes the training program and provides initial evaluation after the first year of the project. The program was successfully incorporated into the residency curricula in family medicine, internal medicine, and psychiatry. Initial evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 18 publications
3
40
0
Order By: Relevance
“…23,31 The values reported in this study correspond to those observed by other SBIRT/MI residency training programs. 32,33 Residents' satisfaction with SBIRT/MI training is important.…”
Section: Discussionsupporting
confidence: 49%
“…23,31 The values reported in this study correspond to those observed by other SBIRT/MI residency training programs. 32,33 Residents' satisfaction with SBIRT/MI training is important.…”
Section: Discussionsupporting
confidence: 49%
“…7 We previously described the implementation of the SBIRT training program with family medicine, general internal medicine, and psychiatry residents that focused on adult patients. 16 The results showed overall satisfaction with the SBIRT training program and regular use in patient care. This paper describes an implementation of the program with pediatric residents and the tailoring of content to the specific care needs of the adolescent population and their families.…”
Section: Introductionmentioning
confidence: 91%
“…The instrument was pilot tested and evaluated for face validity by BCM SBIRT Residency Training Project core team, SBIRT resident and faculty champions, and an MI consultant. 16 …”
Section: Sbirt Self-evaluation Questionnairementioning
confidence: 97%
“…23 Grantee institutions developed training curricula tailored to meet the core SBIRT competencies and skills. Training components used among the SAMHSA grantees, include some or all of the following components with motivational interviewing techniques: didactics, online and web-based content, clinical skills assessment with a standardized patient, and patient encounters within medical specialty settings.…”
Section: Introductionmentioning
confidence: 99%